A Prospective Study of Reconstructive Procedures for Post Burn Hand Contractures - Nasr Hamid Ahmed Al-Qadasi, Nasr Hamid Ahmed Al-Qadasi (Civilization University Journal of Applied and Humanitarian Researches, 2020)
The hand is among the most frequent sites of burns contracture deformity. It represents a common problem and a difficult challenge for many reconstructive surgeons. It is important to restore length, function, and provide good quality skin cover. Our aim is to evaluate the different surgical procedures for resurfacing after release of post burn hand contractures in terms of functional recovery and aesthetic outcome. Totally 30 cases of post burn hand contractures were reconstructed between May 2018 and November 2019 according to site and type of contracture with individualization for each case. All cases were followed up with physiotherapy and splinting devices, functional and aesthetic outcome for each procedure. Results were analyzed as per successful reconstruction, type of procedure, complications, functional and aesthetic outcome. Most of the cases can be resurfaced with skin grafting and few cases have clear indication for flap coverage which needs to be planned and executed cautiously. Z- plasties with proper planning gives maximum length gain with no donor morbidity as other procedures and acceptable appearance. Postoperative physiotherapy and splinting are a must for better outcome in all cases.